Bullying Problem with Emile Durkheim's Structural Functionalism Study - Daniel, Daniel; Bahari, Yohanes (Universitas Tanjungpura, 2024)
The research objective of this article is to explain bullying that occurs within the scope of society by using the Structural Functionalism approach introduced by Emile Durkheim. This research was conducted through a literature study method to explore an in-depth understanding of how the phenomenon of bullying affects social structures and functions in society. The results show that structural functionalism views that each element has a role and function in maintaining social stability. In this study, it is analyzed how bullying affects individuals who are victims, relationships between individuals, and social institutions in society. Bullying can disrupt the balance in the social system and have a negative impact on the victim, including stress, depression and other psychological disorders. In addition, bullying can also create tensions in social relations, both between individuals and between groups in society, thus threatening overall stability. This research also highlights the importance of social norms in maintaining social balance and addressing bullying behavior. Social institutions, such as schools and workplaces, have a role in creating a supportive environment for individuals as well as implementing anti-bullying policies. Through a Structural Functionalism perspective, this article identifies challenges in maintaining social stability and develops solutions to address the problem of bullying in society. This research provides a valuable understanding of the complexity of social interactions and the important role of social norms and social institutions in maintaining social stability in society.